A brief review of the history and philosophy of instrument development in the social sciences - Khairuddin, Khairun Nisa; Omar, Zoharah; Krauss, Steven Eric; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2018)
Instrumentation is the heart of research, with almost all empirical research being heavily dependent upon this aspect. The term is also used interchangeably with other terminologies including measurement, scale, questionnaire and inventory. Despite their ubiquitous usage in the scientific literature, it remains unclear as to whether these terminologies pose the same meaning. Therefore, an enhanced understanding regarding instrument development in the social sciences field is contingent upon a grasp of its history and importance. This paper consists of three parts that expound on: (1) the definition of terms related to an instrument, (2) the history and prominent scholars of instrument development in the social science, and (3) the importance of social science instrumentation. Several academic journals have served as a reference, accompanied by books, reports and online encyclopaedia in ensuring a comprehensive review of the history of instrumentations in the social sciences.